Effect of various interlayers in NiTi to TC4 dissimilar joints by magnetic pulse welding - Zhikang Ye; Timing Zhang; Yuhua Chen; Xiaolong Peng; Yunfa Deng; Shiyi Zhang; Yang Shen; Shanlin Wang; Jilin Xie (Journal of Materials Research and Technology)
Magnetic pulse welding (MPW) has gained wide attention recently. In this paper, the connection of NiTi/TC4 dissimilar materials was achieved by adding pure Al, Cu, and Ni interlayers using MPW technology, and microstructure characterization and mechanical property tests were conducted to evaluate the joints. The results show that the atomic diffusion in the welding process plays a key role in the interface formation process. The interfacial morphology of joints consists of wavy and flat interfaces, and the mechanical interlocking of the wavy interface gives the joints excellent mechanical properties. The joints with the pure Al interlayer have the best mechanical properties, and the tensile shear force is 2.168 kN; the fracture forms of joints with different interlayers are all ductile fractures. In addition, the calculation results of the edge-to-edge crystal matching model show that the side with the high interface mismatch rate is where the joint failure problem occurs frequently.